The use of discretion in prison disciplinary committees - Parton, David A. (American journal of criminal justice, 1987)
Prison disciplinary committees are faced with the formal role responsibility of adjudicating disciplinary cases in an equitable manner and the informal role responsibility of supporting the authority of the staff members who file charges of rule violations by inmates. Analysis of 630 disciplinary cases reveal that dispositional decisions vary according to the number of charged rule violations and that the pattern of the dispositional decisions can be explained by role conflict but not by the thesis that the cases vary in terms of the adequacy of the evidence supporting blameworthiness.